2021
DOI: 10.24272/j.issn.2095-8137.2021.143
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA of the pygmy marmoset type specimen <i>Cebuella pygmaea</i> (Spix, 1823) resolves a taxonomic conundrum

Abstract: The pygmy marmoset, the smallest of the anthropoid primates, has a broad distribution in Western Amazonia. Recent studies using molecular and morphological data have identified two distinct species separated by the Napo and Solimões-Amazonas rivers. However, reconciling this new biological evidence with current taxonomy, i.e., two subspecies, Cebuella pygmaea pygmaea (Spix, 1823) and Cebuella pygmaea niveiventris (Lönnberg, 1940), was problematic given the uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…That said, additional support for the Amazon as a species barrier for pygmy marmosets ( Cebuella spp.) has recently been provided (Boubli et al, 2021; Porter et al, 2021). Notably, many divergences across the Amazon did not occur synchronously and/or postdate the known minimum time of river formation.…”
Section: Discussionmentioning
confidence: 99%
“…That said, additional support for the Amazon as a species barrier for pygmy marmosets ( Cebuella spp.) has recently been provided (Boubli et al, 2021; Porter et al, 2021). Notably, many divergences across the Amazon did not occur synchronously and/or postdate the known minimum time of river formation.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the taxonomy of Amazonian primates is based on the seminal work of Hershkovitz (1977) and has not changed much in the last 45 years. As genomic data becomes more accessible, including data from centuries-old type specimens ( Boubli et al, 2021 ), and as new biodiversity surveys and scientific collections provide new material for rigorous and biologically realistic analyses, our understanding of the taxonomic diversity of Amazonian primates will change ( e.g ., Boubli et al, 2018 , 2019 ; Costa-Araújo et al, 2019 , 2021 ). These taxonomic changes will not be the consequence of taxonomic inflation, but rather will reflect the underlying evolutionary and speciation processes that have generated and are generating the immense Amazonian biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…A phylogenetic study by Boubli et al (2018) showed that the forms Cebuella pygmaea Spix (from the north of the Solimões-Amazonas) and Cebuella niveiventris Lönnberg (from the south of the Rio Solimões-Amazonas) were distinct species. The type locality for Cebuella pygmaea, as given by Spix, was ambiguous but Garbino et al (2019) and Boubli et al (2021) concluded that it is the form to the north of the rios Amazonas-Solimões and Napo, with C. niveiventris being the correct name for the species south of these rivers. Porter et al (2021) confirmed the conclusions of Garbino et al (2019) and Boubli et al (2021) for Ecuador and Peru.…”
Section: Generamentioning
confidence: 99%
“…The type locality for Cebuella pygmaea, as given by Spix, was ambiguous but Garbino et al (2019) and Boubli et al (2021) concluded that it is the form to the north of the rios Amazonas-Solimões and Napo, with C. niveiventris being the correct name for the species south of these rivers. Porter et al (2021) confirmed the conclusions of Garbino et al (2019) and Boubli et al (2021) for Ecuador and Peru. Garbino (2014) reported that Mico manicorensis (Van Roosmalen et al, 2000) was a junior synonym of Mico marcai (Alperin, 1993), previously known only from its type locality on the west bank of the Rio Aripuanã, near the mouth of the Rio Roosevelt.…”
Section: Generamentioning
confidence: 99%